Ekosistem Destinasi Pariwisata Halal Wadah Pengembangan Destinasi Pariwisata Ramah Muslim - Rahtomo, R. Wisnu (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2018)
The ecosystem of halal tourism destinations is a relatively new phenomenon in the practice of tourism destination management and tourism literature. Currently, halal tourism has become part of the completeness of tourist destinations in general. In this article, the development of halal tourism, the concept of ecosystem, as well as the role of various related components in tourism destinations in detail, based on scientific literature and professional practice in the .field of destination management. A critical assessment of the current situation related to the development of halal tourism in Indonesia is also included in this article.